DEVELOPMENT OF LOW IMPACT AEROBIC GYMNASTICS AS AN EFFORT TO PREVENT RHEUMATIC DISEASES IN MOLOTABU VILLAGE - Ucok Hasian Refiater; Arief Ibnu Haryanto (International Journal of Health Science & Medical Research, 2023)
Aerobics is a series of exercises performed for a while to the rhythm of the music. This study aims to develop a low-impact aerobic workout for preventing rheumatic diseases. The initial model for this development was the development of low-impact gymnastics for the elderly Akbid Bina Husada. This research is research and development. Due to the development and implementation of the research procedures in this study, the research procedures were adjusted as follows: Literature research and information gathering; product design; design validation; design revision; product manufacturing; Here are the testers: Material expert tester. Media professionals; product trial topics and usage; The research tool for this development study is a questionnaire adapted from Trisnanda's research in 2018. The data analysis method in this development study uses a descriptive analysis method expressed as a percentage. As a result, evaluation in this study showed that the criteria could be performed very well. Conclusion of this development study is that the resulting product can be used to prevent rheumatic disease